The Use of Contextual Approach for Improving Students' Learning Activities - Yenni Mariska; Supriyono Supriyono; Joko Sutrisno AB; Dian Windriani (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2020)
This study aims to determine efforts to increase learning activities through a contextual approach to students of class VII, MTs Negeri 2 Bandar Lampung in 2019/2020. This research can be used as a reference for one of the learning approaches in order to improve learning achievement. This study uses several data collection methods, such as interviews, tests, observations, and questionnaires. This study shows that the use of contextual learning can increase student learning activities in learning Bahasa Indonesia in class VII MTs Negeri 2 Bandar Lampung. The enhancement of student learning activities in learning Bahasa Indonesia is based on the finding that the average student learning activity in pre-cycle learning is only 49%, it then increases to 72% in the first cycle, and after corrective actions are taken in the second cycle, the learning activities of Bahasa Indonesia are increasing again up to 86%.